Inclusive Music Education: Foreign and Domestic Experience - Azimov D.G. (Scholars Digest Publishing, 2022)
Inclusive education and the very concept of "inclusion" today characterize not only the educational process, but also form the ideological basis of a whole range of pedagogical, social, psychological, anthropological and moral tasks. The word "inclusive" means the acceptance or "inclusion" of persons with educational problems, including disabilities, in the environment of general educational institutions.
Keywords: Music education, inclusive education, pedagogy, anthropological, moral.